Simple ruthenium-catalyzed reductive amination enables the synthesis of a broad range of primary amines - Thirusangumurugan Senthamarai (Nature Portfolio, 2018)
Synthesis of primary amines via operationally simple, inexpensive and environmentally friendly methodologies has high impact in industrial settings. Here, the authors show a reductive amination process involving a ruthenium catalyst, aldehydes/ketones, ammonia, and hydrogen that displays a remarkable scope of primary amine products.